Use and experiences with external fetal monitoring devices among obstetrical providers. (17th July 2020) - Rosenbaum, Alan J.; Smith, Rachel M.; Hade, Erinn M.; Gupta, Ashish; Yilmaz, Alper; Cackovic, Michael
Abstract: Introduction: Fetal heart rate monitoring presents one of the few available methods for evaluating the fetus prior to birth. However, current devices on the market have significant shortcomings. We sought to describe the use and experiences with external fetal monitoring (EFM) devices among obstetrical providers. Materials and methods: We performed a cross-sectional survey in an academic medical center between April and July 2017 including nurse, midwife, and physician obstetrical providers ( n  = 217) who were invited to participate in this study regarding their experiences with the external fetal monitoring (EFM) device utilized by their hospital system in the outpatient, inpatient, and labor and delivery (L&D) settings. Associations between provider characteristics, device use, perception of challenging patients, and potential usefulness of an improved system were assessed by Fisher's exact test. Results: The 137 respondents (63.1%) reported difficulties monitoring obese women (98.5%), multiple gestation pregnancies (90.5%), and early gestational ages (71.5%). Over half (59.5%) of L&D nurses reported interacting with EFM devices for greater than 1-hour during a typical 12-hour shift and fewer than half (42.3%) reported being satisfied with current EFM devices. There were no statistically significant associations between provider age, experience, or time spent utilizing the devices with perception of challenging patient types. Conclusions: In conclusion, obstetrical providers perceive shortcomings of current EFM devices across all levels of provider experience and time utilizing these devices. Nurses reported significant time operating the devices, representing an opportunity to reduce time and costs with an improved device.